2020
DOI: 10.4093/dmj.2019.0138
|View full text |Cite
|
Sign up to set email alerts
|

A Vegetable Dietary Pattern Is Associated with Lowered Risk of Gestational Diabetes Mellitus in Chinese Women

Abstract: Background: Identification of modifiable dietary factors, which are involved in the development of gestational diabetes mellitus (GDM), could inform strategies to prevent GDM. Methods: We examined the dietary patterns in a Chinese population and evaluated their relationship with GDM risk using a case-control study including 1,464 cases and 8,092 control subjects. Propensity score matching was used to reduce the imbalance of covariates between cases and controls. Dietary patterns were identified using factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…The findings are consistent with those of previous studies in other populations (32,35). Notably, previous studies have only confirmed that consumption of single acidic foods (e.g., meat, milk) or alkaline foods (e.g., fruit, vegetables) was associated with the risk of GDM (36)(37)(38)(39); however, taking an integrated approach considering the balance of acidic and alkaline foods may be more important than assessing single acidic and alkaline foods.…”
Section: Discussionsupporting
confidence: 91%
“…The findings are consistent with those of previous studies in other populations (32,35). Notably, previous studies have only confirmed that consumption of single acidic foods (e.g., meat, milk) or alkaline foods (e.g., fruit, vegetables) was associated with the risk of GDM (36)(37)(38)(39); however, taking an integrated approach considering the balance of acidic and alkaline foods may be more important than assessing single acidic and alkaline foods.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that the intestinal microbiota plays a crucial role in response to insulin sensitivity and in underlying inflammatory processes. Considering the microbiota as a therapeutic target in the GDM in addition to the benefits inherent to intestinal health, it also strengthens and intensifies the antiglycant, antioxidant, and anti-inflammatory properties of some bioactive compounds [ 9 , 10 , 11 ]. A possible relationship among the bioavailability, bioactivity, and effects of some bioactive compounds present in natural products to the intestinal microbiota, starting by bacterial conversion, is suggested [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gestational age between 5 and 15 weeks. pregnancy dietary pattern Western pattern: OR = 4.40, 95% CI: 1.58–12.22, p-trend: 0.004); traditional pattern: OR = 4.88, 95% CI: 1.79–13.32, p-trend: 0.002) Chen Q. et al 2020 [ 25 ] China - Asia n: 9556 cases:1464 controls:8092 case-control women who visited the First Affiliated Hospital of Shanxi Medical University in China, 2012–2016. pre-pregnancy and pregnancy dietary pattern Vegetable pattern 1 year prior to conception OR = 0.94; 95% CI: 0.89–0.99, p-trend: 0,025; first trimester of pregnancy OR = 0.94; 95% CI: 0.89–0.99, p-trend: 0,018; second trimester of pregnancy OR = 0.91; 95% CI: 0.86–0.96, p-trend: < 0.001 Zhou X et al 2018 [ 26 ] China - Asia n:2755 cohort pregnant women from the Tongji Maternal and Child Health Cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Second, two cohort and two case-control studies evaluated prepregnancy and pregnancy dietary patterns and GDM risk association in Asia. Chinese women with adherence to a vegetable dietary pattern (consumption of green leafy vegetables, cabbages, carrots, tomatoes, eggplants, potatoes, mushrooms, peppers, bamboo shoots, agarics, and garlic and bean products) prior to conception (OR 0.94; 95% CI, 0.89 to 0.99), during the first trimester (OR, 0.94; 95% CI, 0.88 to 0.99) and during the second trimester of pregnancy (OR, 0.91; 95% CI, 0.86 to 0.96) lowered the GDM risk [ 25 ]. In the same sample, it was determined that the adherence to a vitamin-nutrient pattern (high intake of dietary vitamin A, carotene, vitamin B2, vitamin B6, vitamin C, dietary fibre, folate, calcium, and potassium) 1 year prior to conception (OR: 0.91, 95%CI: 0.86–0.96), in the first trimester (OR: 0.91, 95%CI: 0.86–0.96) and the second trimester of pregnancy (OR: 0.90, 95%CI: 0.85–0.95) decreased GDM risk [ 28 ].…”
Section: Resultsmentioning
confidence: 99%